2013
DOI: 10.1111/phn.12040
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of an International Service Learning Program for Nursing Students

Abstract: Models of reflection need to be explored to select the most appropriate technique to facilitate students' critical reflection in meeting the goals and objectives of the experience. Curriculum integration of global learning, social consciousness, and global cultural competence development is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
46
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 24 publications
3
46
0
1
Order By: Relevance
“…They also can achieve a heightened sense of civic responsibility (Casey & Murphy, 2008;Groh, Stallwood, & Daniels, 2011;Hunt, 2007;Simoni & McKinney, 1998) and an increased willingness to volunteer in the future (Astin, Vogelgesang, Ikeda, & Yee, 2000;Champagne, 2006). Student attitudes and perceptions have been positively altered by increasing caring, leadership, and professionalism (Foli, Braswell, Kirkpatrick, & Lim, 2014;Hwang, Wang, Tu, Chen, & Chang, 2014;Jarosinski & Heinrich, 2010), reducing stigma associated with mental health and substance abuse (Brown, 2009), and heightening sensitivity to cultural diversity (Amerson, 2010;Casey & Murphy, 2008;Curtin, Martins, Schwartz-Barcott, DiMaria, & Ogando, 2013;Jarosinski & Heinrich, 2010). For example, in a community clinic, Chen, McAdams-Jones, Tay, and Packer (2012) compared cultural competence of nursing students who participated in a service learning project, which included reflection, to students who did not.…”
mentioning
confidence: 99%
“…They also can achieve a heightened sense of civic responsibility (Casey & Murphy, 2008;Groh, Stallwood, & Daniels, 2011;Hunt, 2007;Simoni & McKinney, 1998) and an increased willingness to volunteer in the future (Astin, Vogelgesang, Ikeda, & Yee, 2000;Champagne, 2006). Student attitudes and perceptions have been positively altered by increasing caring, leadership, and professionalism (Foli, Braswell, Kirkpatrick, & Lim, 2014;Hwang, Wang, Tu, Chen, & Chang, 2014;Jarosinski & Heinrich, 2010), reducing stigma associated with mental health and substance abuse (Brown, 2009), and heightening sensitivity to cultural diversity (Amerson, 2010;Casey & Murphy, 2008;Curtin, Martins, Schwartz-Barcott, DiMaria, & Ogando, 2013;Jarosinski & Heinrich, 2010). For example, in a community clinic, Chen, McAdams-Jones, Tay, and Packer (2012) compared cultural competence of nursing students who participated in a service learning project, which included reflection, to students who did not.…”
mentioning
confidence: 99%
“…9,[11][12][13]17 The benefits of SL have included but are not limited to professional and doctor-patient communication, cultural competence/awareness, connectedness, normative helping behavior, career benefits, changes in knowledge and attitudes about older adults, awareness of service-providing agencies and community needs, increased awareness of the importance of public health, clinical confidence, utility of history and examination, transformational change, and a reported increase in positive influence on clinical skills 2 years post trip. 9,11,12,[17][18][19] Educational outcomes for SL have been suggested such as personal and interpersonal development, understanding and applying knowledge, engagement curiosity and reflective practice, critical thinking, perspective transformation, and citizenship. 20 Reflection of the experience is a key learning objective to achieve maximal educational benefits.…”
Section: Discussionmentioning
confidence: 99%
“…21 Concerns over SL have also been initially explored and include the concern over the unethical exploitation of vulnerable populations, inability/uncertainty of meeting needs of the patient population, perception of Western medical students as different, navigating different cultures of medicine in regards to privacy, unilateral capacity building in favor of the students, and providing care outside the scope of practice of the students. 11,21,22 Service learning is an area with little published information within chiropractic education. While SL benefits encompass a wide range of educational benefits, this study sought to explore in depth the perceptions of chiropractic students on the development of clinical confidence through a short-term, international SL experience.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, numerous studies have employed a qualitative approach or a combination of qualitative and quantitative approaches to examine program outcomes. [7,16,17] This can be interpreted as resulting from interest in the global nursing field being raised to a relatively higher level through overseas program participation. This is similar to preceding study results that indicated that students' understanding of culture and cultural competency were enhanced through participation in overseas study programs for global health nursing competence.…”
Section: Introductionmentioning
confidence: 99%